Simulated herbicide application between rows of black pepper crops - Ribeiro, Luis Felipe Oliveira; Ribeiro, Maria Eduarda Audizio; Santos, Thavyla Moreira; Aiala, Maria Luisa Carvalho; Vitória, Edney Leandro da (Brazilian Journal of Production Engineering, 2023)
The efficiency of applications through spraying is connected to the capacity to minimize losses by endo-drift and exo-drift while ensuring adequate coverage and deposition on the target surface; the spray nozzles is the main factor connected to application quality. However, few researches focus on technology of application in black pepper crops. The objective of this work was to evaluate the coverage of droplets of simulated herbicide applications using different spray nozzles. The experiment was conducted in a commercial crop area of black pepper of the variety Bragantina, in a randomized block with a 2×2+1 factorial arrangement with four replications per treatment. The nozzles used were XR11002 VP, AI11002 VS, with and without protector (Chapéu de Napoleão) and an additional treatment using the manual backpack sprayer standard nozzle without protector. The results showed that, under these conditions, the nozzle AI11002 VS with protector resulted in adequate coverage and deposition of droplets between rows decreasing the risk of phytotoxicity to black pepper plants. The nozzle XR11002 VP presented higher coverage of droplets in the lower third of black pepper plants. The backpack sprayer standard nozzle resulted in the lowest coverage of droplets between rows.
Keywords: Piper nigrum L.; Densidade de Gotas; Cobertura de Gotas; Tecnologia de Aplicação; Uniformidade